Differences in Plantar Flexor Fascicle Length and Pennation Angle between Healthy and Poststroke Individuals and Implications for Poststroke Plantar Flexor Force Contributions - John W. Ramsay; Thomas S. Buchanan; Jill S. Higginson (Stroke Research and Treatment)
Poststroke plantar flexor muscle weakness has been attributed to muscle atrophy and impaired activation, which cannot collectively explain the limitations in force-generating capability of the entire muscle group. It is of interest whether changes in poststroke plantar flexor muscle fascicle length and pennation angle influence the individual force-generating capability and whether plantar flexor weakness is due to uniform changes in individual muscle force contributions. Fascicle lengths and pennation angles for the soleus, medial, and lateral gastrocnemius were measured using ultrasound and compared between ten hemiparetic poststroke subjects and ten healthy controls. Physiological cross-sectional areas and force contributions to poststroke plantar flexor torque were estimated for each muscle. No statistical differences were observed for any muscle fascicle lengths or for the lateral gastrocnemius and soleus pennation angles between paretic, nonparetic, and healthy limbs. There was a significant decrease (P<0.05) in the paretic medial gastrocnemius pennation angle compared to both nonparetic and healthy limbs. Physiological cross-sectional areas and force contributions were smaller on the paretic side. Additionally, bilateral muscle contributions to plantar flexor torque remained the same. While the architecture of each individual plantar flexor muscle is affected differently after stroke, the relative contribution of each muscle remains the same.